Testing on power plus device for fuel consumption and exhaust emission / Mohd Fauzi Abd. Razak and Khairul Anwar Abdullah - Abd. Razak, Mohd Fauzi; Abdullah, Khairul Anwar (2001)
The trend nowadays for ones consumer products is to be multipurpose. Its designed with less material usage, less weight and easy to use. These product properties were increased by Research and Development (R&D) programmes. Its must given benefits for human being either for environment, or at least be safety for them. POWER PLUS go through about more than 60 years looked for fulfilled that things above. This product claim that it can cut the cost per mile for less petrol or diesel fuel consumption, can reduce the toxic from vehicle emissions, can takes care the engine by giving safety to critical components to stay clean and lubricated. With POWER PLUS any petrol driven vehicle can use standard grade leaded petrol without worrying about lead effect. We not making this report to making rumors or uncertain fact about this product. The test was made with direct observation for fuel consumption, exhaust emission and engine condition with engine idle and without load. Most probably result getting not closer as their claim and we can learn how this occurred. Our suggestion was for enhancing the effort to announce and spread this 'environmental friendship' product to balance with the industrial development process. It also can help to reduce the effect from increasing of fuel price.